Pengaruh Tunjangan Kinerja, Komunikasi, dan Motivasi Kerja Terhadap Kinerja Pegawai pada Kantor Imigrasi Kelas I TPI Polonia Medan - Boyke W. H. Lumban Tobing; Siti Normi; Elperida J. Sinurat (Jurnal Ilmu Manajemen METHONOMIX, 2026)
This study aims to determine and analyze the influence of performance allowances, communication, and work motivation on employee performance at the Polonia Class 1 Immigration Office. This study employed a quantitative approach, which is structured and quantifies data for generalizability. The sample size was 72 respondents. Based on the results of the t-test, it can be concluded that performance allowances influence employee performance, communication influences employee performance, and work motivation influences employee performance. Based on the results of the F-test, it can be concluded that simultaneously, performance allowances, communication, and work motivation have a significant effect on employee performance. The coefficient of determination analysis yielded an Adjusted R Square of 0.683, meaning that 68.3% of employee performance can be explained by performance allowances, communication, and work motivation. The remaining 31.7% (100% - 68.3%) can be explained by other variables not examined in this study.